2019
DOI: 10.1038/s41598-019-53920-w
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of acyl-homoserine lactone (AHL) based bacterial quorum sensing, virulence functions, and biofilm formation by yttrium oxide core/shell nanospheres: Novel approach to combat drug resistance

Abstract: The present study evaluated the efficacy of Y2O3:Tb (core) and Y2O3:Tb@SiO2 nanospheres (core/shell NSs) against virulence functions regulated by quorum sensing (QS) and biofilm formation in pathogenic bacteria. Scanning electron microscope (SEM) images were used to study the size, shape, and morphology. The images clearly displayed spherical shaped, mono-dispersed particles with narrow size distribution and an average grain size of 110–130 nm. The chemical composition of the samples was determined by using en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Listeria monocytogenes ATCC 19,114 and Serratia marcescens ATCC 13,880 were used in the present investigation to assess the antibacterial and antibiofilm activity of the synthesized AuNPs. Antibacterial potential of AuNPs was assessed in terms of MIC using the standard microbroth dilution method described previously [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Listeria monocytogenes ATCC 19,114 and Serratia marcescens ATCC 13,880 were used in the present investigation to assess the antibacterial and antibiofilm activity of the synthesized AuNPs. Antibacterial potential of AuNPs was assessed in terms of MIC using the standard microbroth dilution method described previously [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, SEM results revealed that bacterial bio lm formation can be delayed after exposing the PA to the eucalyptus volatile oil. Bio lm formation is closely related to bacterial resistance (17)(18)(19)(20). Hence, destroying drug resistance is one of the mechanisms of the eucalyptus volatile oil that can be used in clinical bacterial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The environment makes PA more pathogenic, and this process is mainly controlled by these 4 systems (14,21). The characteristics of many PA virulence factors and distinct genes is principally regulated by 2 acyl-homoserine lactone (AHL) QS systems, LasI/LasR and RhlI/RhlR (8,20). LasR is central to the QS system (22).…”
Section: Basic Knowledge Of Qs Of Pamentioning
confidence: 99%
“…The structure-activity relationship controlling LasR antagonism by V-06-018 has been reported. V-06-018 is a comparatively effective LasR antagonist in both Escherichia coli and PA LasR reporter strains and has been confirmed to inhibit virulence-related genes and phenotypes in PA (8). At the same time, V-06-018 lacks lactone parts so it is not easily hydrolyzed or enzymatically decomposed by AHL lactonases.…”
Section: Lasr Antagonist V-06-018mentioning
confidence: 99%
See 1 more Smart Citation